An Analysis of Legal Considerations of Judicial Decisions on Customary Land Disputes: A Comparison of Indonesia and Africa - Safrin Salam; La Gurusi; La Ode Muhammad Karim; Cynthia C. Izu; Supriyanto; Rasmala Dewi (Jurnal Jurisprudence, 2025)
ABSTRACT Purpose of the Study: This research aims to analyze judges’ legal considerations in adjudicating Decision No. 20/pdt/2021/PTKDI as well as to find the implications of legal changes on customary land regulations in Kondowa Village, Buton Regency, Southeast Sulawesi Province, Indonesia. Methodology: This research employed the normative juridical method with the statute approach, the case approach, and the conceptual approach. The data were sourced from primary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Results: In Decision No. 20/pdt/2021/PTKDI, judges gave legal considerations of the decision based on inapplicable regulations. They ignored the existence of customary laws from the Kampirina Customary Institution. There are different perspectives on the indigenous rights concept as well as the legality of registering customary land. Apart from that, there are different interpretations on the Kampirina Customary Institution’s legality which is based on the Regional Regulation of Buton Regency No. 4 of 2015 on Customary Institutions and Regulation of the Ministry of Internal Affairs No. 52 of 2014 on the Guidelines to Acknowledging and Protecting Indigenous Societies. The legal implication of Decision No. 20/pdt/2021/PTKDI includes changes in the customary law on the regulations regarding customary land as well as the validity of indigenous rights from the Kampirina Customary Institution. Applications of this Study: This research can be applied by giving insight into judges’ logical dynamics in creating logical legal considerations according to the applicable regulations. Novelty/Orginality of this Study: This research offers novelty as judges’ legal considerations were analyzed using the customary law as well as the justice awareness theory, the reality theory, and the decision theory that apply in the customary law. This research yielded an analysis of judges’ legal considerations based on the customary law and the positive law that creates a sense of justice for indigenous people. Keywords: Judicial Decision, Customary Land, Customary Law, Legal Reasoning, Indonesia.   ABSTRAK  Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis pertimbangan hukum hakim dalam mengadili Putusan No. 20/pdt/2021/PTKDI serta menemukan implikasi perubahan hukum terhadap peraturan pertanahan adat di Desa Kondowa, Kabupaten Buton, Provinsi Sulawesi Tenggara, Indonesia. Metodologi: Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual. Data bersumber dari data primer yang terdiri dari bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Hasil: Dalam Putusan No. 20/pdt/2021/PTKDI, hakim memberikan pertimbangan hukum atas putusan tersebut berdasarkan peraturan perundang-undangan yang tidak berlaku. Hakim mengabaikan keberadaan hukum adat dari Lembaga Adat Kampirina. Terdapat perbedaan perspektif mengenai konsep hak ulayat serta legalitas pendaftaran tanah adat. Selain itu, terdapat perbedaan penafsiran mengenai legalitas Lembaga Adat Kampirina yang didasarkan pada Peraturan Daerah Kabupaten Buton No. 4 Tahun 2015 tentang Lembaga Adat dan Peraturan Menteri Dalam Negeri No. 52 Tahun 2014 tentang Pedoman Pengakuan dan Perlindungan Masyarakat Hukum Adat. Implikasi hukum dari Putusan No. 20/pdt/2021/PTKDI antara lain perubahan hukum adat terkait pengaturan tanah adat serta keabsahan hak ulayat Lembaga Adat Kampirina. Aplikasi Penelitian: Penelitian ini dapat diaplikasikan dengan memberikan wawasan mengenai dinamika logika hakim dalam merumuskan pertimbangan hukum yang logis sesuai dengan ketentuan yang berlaku. Kebaruan/Keaslian Penelitian: Penelitian ini menawarkan kebaruan karena pertimbangan hukum hakim dianalisis menggunakan hukum adat serta teori kesadaran keadilan, teori realitas, dan teori putusan yang berlaku dalam hukum adat. Penelitian ini menghasilkan analisis pertimbangan hukum hakim berdasarkan hukum adat dan hukum positif yang menciptakan rasa keadilan bagi masyarakat adat. Kata Kunci: Putusan Pengadilan, Tanah Adat, Hukum Adat, Penalaran Hukum, Indonesia